1994
DOI: 10.3109/00016359409027591
|View full text |Cite
|
Sign up to set email alerts
|

Predictor evaluation of postoperative morbidity after surgical removal of mandibular third molars

Abstract: The effect of several pre- and per-operative variables on indicators of postoperative morbidity was assessed in 204 patients after unilateral mandibular third-molar surgery. The variables included gender, age, use of tobacco and alcohol, state of eruption, depth and angulation of the tooth, duration of the operation, pericoronitis, and time of day of surgery. Visual analogue scales were used for patient assessment of pain and swelling and for clinical assessment of swelling. Maximum pain was indicated 6 h post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
1
4

Year Published

1995
1995
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 25 publications
2
56
1
4
Order By: Relevance
“…15,16 In our study, a previous history of dry socket was an important factor in determining whether a patient returned with pain. This agrees with work by Berge and Boe, 17 which indicated that as yet unidentified intrinsic factors influenced post operative healing. The fibrinolytic theory 18 states that dry socket is the result of loss of the blood clot caused by bone fibrinolysis.…”
Section: Bacteria Play No Part In the Development Of Dry Socketsupporting
confidence: 82%
“…15,16 In our study, a previous history of dry socket was an important factor in determining whether a patient returned with pain. This agrees with work by Berge and Boe, 17 which indicated that as yet unidentified intrinsic factors influenced post operative healing. The fibrinolytic theory 18 states that dry socket is the result of loss of the blood clot caused by bone fibrinolysis.…”
Section: Bacteria Play No Part In the Development Of Dry Socketsupporting
confidence: 82%
“…To date, few studies have described an incidence of IAN injury less than 1% [6][7][8][9][10][11][12] . Thus, after calculation we obtained a sample (n) of 132 patients, with a confidence interval of 95% and a sampling error of 7%.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have reported outcomes for selected lifestyle measures after surgery. [6][7][8][9][10] Here, we report both clinical and HRQOL outcomes after third molar surgery in patients who were treated in a prospective, clinical trial conducted at multiple clinical sites, including community and academic practices.…”
mentioning
confidence: 99%